Effects of organic matter application on methane emission from paddy fields adopting organic farming system - P Nungkat; Z Kusuma; E Handayanto (Journal of Degraded and Mining Lands Management, 2015)
A study that was aimed to determine the effect of the use of organic manure and azolla on methane emission on paddy field of organic systems was conducted on paddy fields in the Gempol Village, Sambirejo District of Sragen Regency, Indonesia. The experimental design performed for this study was a completely randomized block design consisting of three factors; the factor I was rice cultivars (Mira-1; Mentik Wangi; Merah Putih); factor II was dose of organic manure (0 t/ha and 10 t/ha) and factor III was Azolla inoculums dose (0 t/ha and 2 t/ha). Gas sampling was conducted 3 times in one growing season when the rice plants reached ages of 38, 66 and 90 days after planting. The results showed that there was no correlation between the uses of organic fertilizers for rice production on methane emission. The increase of methane emission was very much influenced by the redox potential. Methane emission from Mira-1 field was higher than that from Mentik Wangi and Merah Putih fields. Emission of methane gas from Mira-1 field ranged from -509.82 to 791.34 kg CH4/ha; that from Wangi ranged from -756.77 to d 547.50 kg CH4/ha and that from Merah Putih ranged from -399.63 to 459.94 kg CH4/ha. Application of 10 t organic manure /ha and 2 t azolla/ha in Mentik Wangi reduced methane emissions with a high rice production compared to Merah Putih and Mira-1.